Justice in organizations and its impact on Organizational Citizenship Behaviors: A multidimensional approach - Asaad Hameed Al-ali (Taylor & Francis Group, 2019)
This research was aimed at investigating the impact of multifocal organizational justice on Organizational Citizenship Behaviors (OCBs). Using convenience sampling, a questionnaire was administered to (330) employees in Jordanian pharmaceutical industry companies. The research adopted well validated measures for multifocal organizational justice (distributive, procedural, and interpersonal) and also for measuring OCBs. The results of hierarchical multiple regression analysis showed that overall organizational justice predicted (40%) of the variance in OCBs. Agent-referenced organizational justice was found to be a stronger predictor of OCBs than system-referenced organizational justice. Moreover, this research has pinpointed interpersonal justice as being the strongest predictor of OCBs. The research recommended the Jordanian pharmaceutical industry companies retain and employ direct supervisors who have the necessary awareness and understanding of the importance of their role in encouraging OCBs as well as the necessary experience for this role.